2020
DOI: 10.1164/rccm.202002-0251st
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Detection of Sarcoidosis. An Official American Thoracic Society Clinical Practice Guideline

Abstract: Background: The diagnosis of sarcoidosis is not standardized but is based on three major criteria: a compatible clinical presentation, finding nonnecrotizing granulomatous inflammation in one or more tissue samples, and the exclusion of alternative causes of granulomatous disease. There are no universally accepted measures to determine if each diagnostic criterion has been satisfied; therefore, the diagnosis of sarcoidosis is never fully secure. Methods: Systematic reviews and, when appropriate, meta-analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
581
4
37

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 656 publications
(626 citation statements)
references
References 175 publications
4
581
4
37
Order By: Relevance
“…2 In addition, the recently published Clinical Practice guideline for sarcoidosis published by the American Thoracic Society (ATS) recommend initial screening with echocardiography in patients who are suspected of PH. 59 According to the recently published ATS clinical guideline for sarcoidosis, 59 suspicion of PH is based on clinical manifestations including disproportional dyspnea (e.g., disproportional in relation to pulmonary function tests), exertional chest pain and/or syncope, prominent P2 or S4 during physical examination, reduced 6-minute walk distance (6MWD), desaturation with exercise, reduced diffusing capacity for carbon monoxide (DLCO), increased pulmonary artery diameter relative to ascending aorta diameter, elevated brain natriuretic peptide (BNP), and/or fibrotic lung disease.…”
Section: Diagnosis and Clinical Featuresmentioning
confidence: 99%
“…2 In addition, the recently published Clinical Practice guideline for sarcoidosis published by the American Thoracic Society (ATS) recommend initial screening with echocardiography in patients who are suspected of PH. 59 According to the recently published ATS clinical guideline for sarcoidosis, 59 suspicion of PH is based on clinical manifestations including disproportional dyspnea (e.g., disproportional in relation to pulmonary function tests), exertional chest pain and/or syncope, prominent P2 or S4 during physical examination, reduced 6-minute walk distance (6MWD), desaturation with exercise, reduced diffusing capacity for carbon monoxide (DLCO), increased pulmonary artery diameter relative to ascending aorta diameter, elevated brain natriuretic peptide (BNP), and/or fibrotic lung disease.…”
Section: Diagnosis and Clinical Featuresmentioning
confidence: 99%
“…1,2 The diagnosis of sarcoidosis is based on a compatible clinical presentation in combination with a biopsy showing granulomatous inflammation and exclusion of alternative diagnoses with similar presentations. 3 The tendency of sarcoidosis to present with nonspecific clinical findings in the absence of a diagnostic biomarker and the promiscuous association of granulomatous inflammation with multiple diseases often results in a delayed diagnosis. 4 Further clouding the picture is the association and possible co-occurrence of sarcoidosis with other diseases that share overlapping clinical and histologic features.…”
mentioning
confidence: 99%
“…I reviewed the abstract or text of the case series cited by the authors of the guideline policy ( 2 ) and found that most confounded their analysis by conflating BHL with cases demonstrating radiographically evident mediastinal lymphadenopathy, a feature characteristic of lymphoma. Collectively, they reported 1.96% with an AD, more than 100-fold a prior estimate in which ADs presented as ABHL ( 3 ).…”
mentioning
confidence: 99%